Efektivitas Video Edukasi terhadap Pengetahuan dan Keterampilan Kader Posyandu di Wilayah Kerja Puskesmas Mojolaban - Rima Very Prasetyaningrum; Titik Haryanti; Farid Setyo Nugroho; Prita Devy Igiany (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Community-Based Health Efforts (UKBM) such as Integrated Service Post (Posyandu) improve public health through promotive and preventive measures. The Posyandu cadre evaluation in Plumbon Village, under the Mojolaban Community Health Center, found that all cadres were still Purwa, with poor knowledge and competence in 25 fundamental cadre competencies. The constraints of traditional learning approaches contribute to inadequate cadre competency enhancement. This research examines how instructional video media improves Posyandu cadres' 25 fundamental cadre competencies. A quantitative pre-experimental one-group pretest-posttest design was adopted in this investigation. The research sample included 46 Plumbon Village Posyandu cadres chosen using total sampling. Health education was provided via videos and talks. Knowledge and skills questionnaires were used before and after the session. The Wilcoxon Signed Rank Test was used for univariate and bivariate data analysis. Posttest scores increased for all cadres compared to pretest. The Wilcoxon test showed a significant difference between pretest and posttest scores (p < 0.05). This shows that instructional video media improves Posyandu cadres' knowledge and abilities. Video helps people grasp and retain knowledge by presenting it visually and audibly.